Resource Description Language: A Unified Description Language for Network Embedded Resources - André C. Santos; Luís D. Pedrosa; Martijn Kuipers; Rui M. Rocha (International Journal of Distributed Sensor Networks, 2012)
As machine-to-machine networks become larger and more pervasive, manual configuration and discovery of resources will become intractable. It is in this context that we propose the RDL, a Resource Description Language that represents a uniform way of describing embedded resources, allowing them to be shared and enabling a new class of resource-aware applications. The RDL can describe a wide range of resources, characterizing individual nodes or entire networks. It can contribute to overcome performance issues in dense networks or mobility-driven problems in highly dynamic machine-to-machine topologies by providing the means for self-adaptability and manageability, as well as opportunistic resource sharing in context-aware embedded applications. The main goal for the RDL is to define a reusable and extensible resource description specification, which can only be reached if the resources are described in a standardized format. To illustrate the feasibility of our approach, we have also developed a Java implementation of the RDL framework, as well as a TinyOS implementation targeting resource constrained platforms. Furthermore, we have developed Modulus, a modular middleware for the development of resource-aware distributed applications.